Boosting trade through flexible rules of origin in preferential agreements - Jaime De Melo; Julien Gourdon; Karin Gourdon (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
Rules of origin are critical components of preferential trade agreements designed to stop products coming in under insufficient transformation or through the partner that applies the lowest tariff. But in practice, these rules are often needlessly complex, undoing the benefits of market access associated with trade agreements. This column reports research showing that the adoption of more flexible product- specific rules of origin within preferential agreements would give a significant boost to global trade.
Keywords: 330; Rules of origin